2018
DOI: 10.4172/pharmaceutical-sciences.1000407
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Conversion of Racemic Sotalol to R(-)-Sotalol by Lipase AP6

Abstract: Most pharmaceutical compounds have asymmetric nature and are optically active. Compounds with one asymmetric centre (chiral centre) would exhibit two enantiomeric forms and among them one is pharmacologically active (eutomer) while the other one contributed side effects or toxic effects or totally inert (distomer) [1] . Hence, current interest is towards development and administration of eutomer instead of its racemic mixture to improve therapeutic efficacy and reduce the unwanted effects due to the distomer [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…were the highest results recorded during the observation.The E (62) value in this study was found to be moderate (i.e., 20-100)(Swetha et al, 2018) when the reaction was catalyzed by free Candida antarctica lipase B and the value was slightly higher than the E value obtained byBarbosa et al (2010), which recorded a value of 57 in Candida antarctica B lipase-catalyzed esterification of (RS)propanolol. The researchers have thus concluded the enol esters (i.e., commonly vinyl acetate) have higher efficiency in organic solvents in esterification due to their high reactivity in serine residues from the catalytic site of lipases (Banoth et al 2015; Barbosa et al 2010; Dwivedee et al 2015; Agustian et al 2016).…”
contrasting
confidence: 76%
“…were the highest results recorded during the observation.The E (62) value in this study was found to be moderate (i.e., 20-100)(Swetha et al, 2018) when the reaction was catalyzed by free Candida antarctica lipase B and the value was slightly higher than the E value obtained byBarbosa et al (2010), which recorded a value of 57 in Candida antarctica B lipase-catalyzed esterification of (RS)propanolol. The researchers have thus concluded the enol esters (i.e., commonly vinyl acetate) have higher efficiency in organic solvents in esterification due to their high reactivity in serine residues from the catalytic site of lipases (Banoth et al 2015; Barbosa et al 2010; Dwivedee et al 2015; Agustian et al 2016).…”
contrasting
confidence: 76%
“…There are several advantages for single enantiomer products when compared to their racemates like more selective and comparatively simple pharmacodynamic as well as pharmacokinetic profile, potential for an improved therapeutic index and very less probability for complex drug interactions [1]. Though there are quite a few ways to obtain chiral molecules in commercially pure form like resolution of racemates, chiral pool synthesis, laboratory-invented chiral building blocks, asymmetric synthesis and bio-transformations, no single method is ideal.…”
Section: Introductionmentioning
confidence: 99%
“…Though there are quite a few ways to obtain chiral molecules in commercially pure form like resolution of racemates, chiral pool synthesis, laboratory-invented chiral building blocks, asymmetric synthesis and bio-transformations, no single method is ideal. Hence combination of biotransformation with chromatographic resolution [1] was employed in the present study. Development of a single enantiomer from a previously marketed racemate is known as chiral switch [2] and there are different new resolution procedures for obtaining pure enantiomer from a racemic mixture with 100% yield, theoretically, like dynamic kinetic resolution, stereoinversion by deracemization, cyclic racemization and enantioconvergent processes, etc.…”
Section: Introductionmentioning
confidence: 99%